Integration of Science Education, Transcendental Ethics, and Legal Literacy in Reproductive Health as a Preventive Effort against the Circulation of Illegal Abortion Drugs: A Review - Noor Rahmad; Absori; Rizka (Postgraduate, University of Mataram, 2026)
Abortion represents a public health challenge at the intersection of clinical safety, ethics, and law; limitations on access to safe abortion services are likely to incite a channel push to informal/illegal abortion, specifically via digital modalities. The legal framework in Indonesia is primarily restrictive with limited exceptions, which means that uncertainty around legal boundaries, stigma and barriers to accessing care can generate demand for information and illegal abortions. This study combines an evidence mapping integrated review using the PICo/PEO framework to synthesize the cross-disciplinary evidence across three pillars, including sexual-reproductive health (SRH) science, transcendental ethics, and legal literacy (criminal–health–pharmaceutical–digital regulation). The search was performed through health, education and legal databases and a two-stage selection process as per the PRISMA principles and extraction was performed from a thematic-operational matrix. The review invariably found that the strongest prevention hinges on the development and implementation of a three-pillar curriculum, along with case/vignette-based pedagogy, medico-legal risk literacy, and online information sorting competency. Evidence mapping the strengthening of legal literacy and design due diligence platform as a strategic node to reduce demand and suppress the circulation of illegal abortion drugs.